Punching shear in waffle slabs in the presence of biaxial moment transfer - Fong, Dickson Wen Jing (2018)
An extensive amount of works have been carried out to develop the current understanding in punching shear mechanism noted in reinforced concrete slabs. However, despite the increasing popularity of waffle slabs, the current understanding about punching behaviour is mainly focused on solid flat slabs, and only limited amount of works have been carried out on waffle slabs and in the presence of biaxial moment. Thus, there is a need to carry out a research in this area to aid the understanding about punching mechanism of waffle slabs in the presence of biaxial moment for the internal column and edge column connections.